Rapid directional changes associated with a 6.5 kyr-long Blake geomagnetic excursion at the Blake-Bahama Outer Ridge - Bourne, M; Mac Niocaill, C; Thomas, A; Knudsen, M; Henderson, G (2012)
Geomagnetic excursions are recognized as intrinsic features of the Earth's magnetic field. High-resolution records of field behaviour, captured in marine sedimentary cores, present an opportunity to determine the temporal and geometric character of the field during geomagnetic excursions and provide constraints on the mechanisms producing field variability. We present here the highest resolution record yet published of the Blake geomagnetic excursion (~125ka) measured in three cores from Ocean Drilling Program (ODP) Site 1062 on the Blake-Bahama Outer Ridge. The Blake excursion has a controversial structure and timing but these cores have a sufficiently high sedimentation rate (~10cmka -1) to allow detailed reconstruction of the field behaviour at this site during the excursion. Palaeomagnetic measurements of the cores reveal rapid transitions (<500yr) between the contemporary stable normal polarity and a completely reversed state of long duration which spans a stratigraphic interval of 0.7m. We determine the duration of the reversed state during the Blake excursion using oxygen isotope stratigraphy, combined with 230Th excess measurements to assess variations in the sedimentation rates through the sections of interest. This provides an age and duration for the Blake excursion with greater accuracy and with constrained uncertainty. We date the directional excursion as falling between 129 and 122ka with a duration for the deviation of 6.5±1.3kyr. The long duration of this interval and the fully reversed field suggest the existence of a pseudo-stable, reversed dipole field component during the excursion and challenge the idea that excursions are always of short duration. © 2012 Elsevier B.V.